2020
DOI: 10.1186/s12891-020-03710-7
|View full text |Cite
|
Sign up to set email alerts
|

Cervical rotation, chest deformity and pelvic obliquity in patients with spinal muscular atrophy

Abstract: Background Musculoskeletal disorders are often observed in patients with spinal muscular atrophy (SMA). The aim of the study was to assess passive ranges of rotation in the cervical spine, chest deformity and pelvic obliquity in SMA patients, and to compare these results to the norms obtained in the group of healthy individuals. The second aim was to review these measurements and Cobb angle values for correlations in SMA patients. Methods The study included 74 patients with SMA and 89 healthy individuals age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The impact of scoliosis on the ranges of neck rotation and other postural parameters in 74 children with SMA1, SMA2, and SMA3 (not treated pharmacologically) was discussed in an earlier study by Stępień et al The authors, in addition to the limitations of the range of cervical rotation, showed that the ranges of neck rotation, chest shape, and pelvic alignment are interrelated and depend on the prevalence of scoliosis, age, and the type of SMA. Children with SMA1 and SMA2 showed more severe deformities and movement limitations, compared to the SMA3 and control groups [8]. Fujak et al, when analyzing the natural development of scoliosis, observed that the oblique position of the pelvis is common in children with SMA, including the youngest ones, and it is more severe in the SMA2 group, compared to the SMA3 type [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of scoliosis on the ranges of neck rotation and other postural parameters in 74 children with SMA1, SMA2, and SMA3 (not treated pharmacologically) was discussed in an earlier study by Stępień et al The authors, in addition to the limitations of the range of cervical rotation, showed that the ranges of neck rotation, chest shape, and pelvic alignment are interrelated and depend on the prevalence of scoliosis, age, and the type of SMA. Children with SMA1 and SMA2 showed more severe deformities and movement limitations, compared to the SMA3 and control groups [8]. Fujak et al, when analyzing the natural development of scoliosis, observed that the oblique position of the pelvis is common in children with SMA, including the youngest ones, and it is more severe in the SMA2 group, compared to the SMA3 type [7].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal muscular atrophy (SMA) is a rare genetic disease [1] that leads to many limitations in the daily functioning of the affected persons and their families. The disease has a progressive course, featuring weakened muscle strength [2][3][4][5][6], progressive deformities of the spine and chest [7,8], limitations of the range of motion (ROM) in the cervical spine and limb joints [8][9][10], respiratory disorders, and the gradual deterioration of the functional status [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In 95% of cases, SMA is caused by deletion and/or mutation in the survival motor neuron 1 (SMN1) gene on chromosome 5, which results in insufficient production of the survival motor neuron (SMN) protein [ 1 , 3 ]. It manifests as muscle flaccidity and gradual atrophy, resulting in progressing functional limitations [ 3 , 4 ]. Motor development is known to regress in untreated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal orthosis is recommended if the child has Cobb's angle of more than 20 degrees with hypotonic trunk [1]. Distortion of the rib cage related to scoliosis is associated with respiratory disease, and pelvic obliquity associated with scoliosis affects the ability to maintain balance in the sitting position [25]. Furthermore, hip dislocation or subluxation is common in people with SMA [26].…”
Section: Management Of Musculoskeletal Deformities Including Scoliosis and Hip Dislocationmentioning
confidence: 99%